Primary Merkel vulvar cell carcinoma - Torres-Cepeda, Duly (2022)
Merkel cells were originally described in the stratum basale of the epidermis withneuroendocrine properties. Merkel cell carcinoma of the vulva is an extremelyrare and highly aggressive neoplasm. There are few cases of these tumors, mostof which have been considered neuroendocrine tumors. The histologic origin andetiology of this disease are controversial. It is known for his aggressive behaviorand propensity for early diffusion. Because of its rarity in this location, it is unclearwhether it behaves differently from similar skin carcinomas in other locations. A caseof primary vulvar Merkel cell carcinoma is presented. Excisional biopsy examinationrevealed a 4 x 3-centimeter tumor in the posterior third of the left labium majus of thevulva without lymph node involvement. The patient underwent radical vulvectomyand bilateral inguinal lymph node dissection. Postoperative histological evaluationshowed no regional or distant metastases.